THE IMPORTANCE OF NURSING SUPPORT IN ORGANIZING AND ASSESSING REHABILITATION PROCESSES IN BRONCHIAL ASTHMA - Usmanova Zarifa Turgunovna (Modern American Journals, 2025)
This article on bronchial asthma with sick patients' rehabilitation processes, organizational growth, and nursing evaluation helps illuminate. Nurses' patient education, treatment to the mode of compliance to reach provision, rehabilitation programs coordination, and clinical and psychological situation in the evaluation role analysis Diagrams through nursing interventions structure and assessment indicators are visually in appearance presented is being done.
Keywords: Bronchial asthma, rehabilitation, nursing help, life quality, evaluation.